INTERCULTURAL PECULIARITIES OF CORRUPTION PERCEPTION UNDER CONDITIONS OF SUSTAINABLE DEVELOPMENT - Kubko, Valentyna (Current Problems of Sustainable Development, 2026)
The article examines the intercultural features of corruption perception under conditions of sustainable development and identifies the influence of socio-cultural factors on the formation of attitudes toward corrupt practices in the contemporary international environment. It is substantiated that corruption should be considered not only as a legal, political, or economic issue but also as a complex socio-cultural phenomenon shaped by historical traditions, political culture, institutional trust, communication patterns, and models of social interaction. Differences in corruption perception across countries significantly affect the effectiveness of anti-corruption policies and complicate the development of universal approaches to combating corruption. The study emphasizes the importance of an intercultural approach through the application of cross-cultural theories. Particular attention is devoted to the concepts developed by Geert Hofstede, including power distance, individualism, and collectivism, as well as Edward Hall’s theory of high-context and low-context cultures, which explain how cultural characteristics influence public attitudes toward corruption practices and informal institutional interactions. The article argues that corruption perception is strongly influenced by political culture, institutional development, democratic maturity, and social norms. Countries characterized by stronger democratic institutions, transparency mechanisms, and higher public accountability generally demonstrate lower levels of tolerance toward corruption. Conversely, societies with weaker institutional structures and stronger informal networks often face greater challenges in implementing effective anti-corruption mechanisms. Special attention is devoted to the relationship between corruption and sustainable development. Corruption negatively affects institutional resilience, social trust, public administration efficiency, and investment attractiveness, thereby creating barriers to achieving the United Nations Sustainable Development Goals, particularly Sustainable Development Goal 16 “Peace, Justice and Strong Institutions”. An authorial typology of models of public perception of corruption is proposed, and a comparative analysis of selected countries is conducted, taking into account socio-cultural factors and international corruption assessment indicators. The article also analyzes the analytical value of the Corruption Perceptions Index (CPI) developed by Transparency International as an international measurement instrument for evaluating corruption perception and conducting comparative international analysis. Particular attention is paid to Ukraine, whose anti-corruption transformation occurs under conditions of European integration, institutional modernization, and full-scale war. The findings demonstrate that strengthening anti-corruption culture and institutional resilience is becoming an important prerequisite for sustainable development and long-term democratic transformation.